2019
DOI: 10.3390/molecules24132501
|View full text |Cite
|
Sign up to set email alerts
|

Hybrid Solid-Phase Extraction for Selective Determination of Methamphetamine and Amphetamine in Dyed Hair by Using Gas Chromatography–Mass Spectrometry

Abstract: Sample preparation is an important step in the isolation of target compounds from complex matrices to perform their reliable and accurate analysis. Hair samples are commonly pulverized or processed as fine cut, depending on preference, before extraction by techniques such as solid-phase extraction (SPE), liquid–liquid extraction, and other methods. In this study, a method based on hybrid solid-phase extraction (hybridSPE) and gas chromatography–mass spectrometry (GC–MS) was developed and validated for the dete… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(2 citation statements)
references
References 27 publications
0
2
0
Order By: Relevance
“…The results are shown in Table 1 . The average spiked recovery values of methamphetamine at high, medium, and low concentrations were 88.9 ± 0.7%, 85.5 ± 0.3%, and 84.3 ± 2.6%, respectively, with an RSD of 2.9%, which indicated that the method had good recovery values [ 60 ].…”
Section: Resultsmentioning
confidence: 99%
“…The results are shown in Table 1 . The average spiked recovery values of methamphetamine at high, medium, and low concentrations were 88.9 ± 0.7%, 85.5 ± 0.3%, and 84.3 ± 2.6%, respectively, with an RSD of 2.9%, which indicated that the method had good recovery values [ 60 ].…”
Section: Resultsmentioning
confidence: 99%
“…Hair analysis can be used to determine the concentration of many licit or illicit drugs in their parent or metabolized form such as nicotine, the biomarker of tobacco exposure [40][41][42]; ethyl glucuronides (EtG) and total fatty acid ethyl esters (FAEEs), which are biomarkers of ethanol intake [43][44][45][46]; cannabis [47][48][49][50]; cocaine [51][52][53][54]; amphetamines [55][56][57]; and NPS, including phenethylamines, piperazines, synthetic cathinones and synthetic cannabinoids [58,59].…”
Section: Hairmentioning
confidence: 99%